Design and Simulation of Portable Paving Vehicle for Straw Checkerboard Barriers - Zuntao Peng; Mingrun Jia; Jingrong Fang; Feng Jiang (Machines)
Paving straw checkerboard barriers in the desert is an efficient measure of wind break and sand fixation. Generally, straw checkerboard barriers are paved manually. Focusing on the low automation level of straw checkerboard barrier paving, a portable paving vehicle for straw checkerboard barriers was designed in this paper. First, the portable paving vehicle for straw checkerboard barriers was designed using SolidWorks, and the design contents include a grass insertion mechanism, an intermittent transmission mechanism, a metamorphic mechanism, and motor and power supply. Then, the load test of the grass insertion mechanism was carried out to determine the maximum force load of 25 N during the grass insertion process, and the strength of the rocker and the horizontal slide rod were checked. Among them, the safety factor of the rocker rod and the horizontal slide rod were 1 and 1.5, respectively, and the allowable stress of the rocker rod and the horizontal slide rod was 27.3 MPa and 205 MPa. The maximum stresses of 0.92 MPa and 67 MPa were less than the allowable stresses, which meet the strength requirements. In order to verify the design principle and the results of the strength check, the grass insertion mechanism, rocker, and horizontal slide rod were analyzed by using ABAQUS. The results show that the grass insertion mechanism has an obvious rapid return characteristic, which is in agreement with the design principle. At the same time, the maximum stress of the rocker rod and the horizontal slide rod was 1 MPa and 36 MPa, respectively, which meets the strength requirements. Finally, the physical prototype was manufactured and its running state was verified. The results show that the physical prototype can pave the straw checkerboard sand barrier on the sand normally, and the portable paving vehicle for straw checkerboard barriers can be a reference for other sand-control vehicles and provide an effective way of paving straw checkerboard barriers to control desertification.